REGIONAL REVENUE AND EXPENDITURE BUDGET TO ANALYZE THE ECONOMIC CONDITION OF BOJONEGORO REGENCY IN 2011 - 2022 - Putri, Ria Amelia; Susilo, Joko Hadi; Astuti, Hartiningsih; Vellyana, Salsa Devi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to analyze Capital Expenditures from Special Allocation Funds and Regional Taxes on the economic conditions of Bojonegoro Regency in 2011-2022.  This research uses a quantitative analysis approach with a descriptive approach, the data used in this research is time series data with a period of 12 (twelve) years from 2011 - 2022 with all annual data on capital expenditure, Special Allocation Fund, regional taxes and economic growth for Bojonegoro district obtained through the Central Statistics Agency (BPS). Data analysis techniques in this research use the Classic Assumption Test, Multiple Linear Regression Analysis, and Partial Test (T), Simultaneous Test (F), Determination Test, with the help of the eviews 12 analysis tool. The results of the Partial Test (T) show that Shopping capital does not have a significant effect on economic growth, Special Allocation Fund has a significant effect on economic growth, Regional Taxes do not have a significant effect on Economic Growth. Based on the results of the Simultaneous Test (F), it shows that Special Allocation Fund Capital Expenditures and Regional Taxes simultaneously have a significant effect on the Economic Growth Conditions of Bojonegoro Regency in 2011 - 2022.